Improving stereoselectivity of phosphotriesterase (PTE) for kinetic resolution of chiral phosphates - Jaito, Nongluck; Phetlum, Suthathip; Saeoung, Titiporn; Tiyasakulchai, Thanat; Srimongkolpithak, Nitipol; Uengwetwanit, Tanaporn (Frontiers in Bioengineering and Biotechnology, 2024)
Specific stereoisomer is paramount as it is vital for optimizing drug efficacy and safety. The quest for the isolation of desired stereoisomer of active pharmaceutical ingredients or key intermediates drives innovation in drug synthetic and biocatalytic methods. Chiral phosphoramidate is an important building block for the synthesis of antiviral drugs such as remdesivir and sofosbuvir. Given the clinical potency of the (Sp)-diastereomer of the drugs, an enzyme capable of completely hydrolyzing the (Rp)-diastereomer is needed to achieve the purified diastereomers via biocatalytic reaction. In this study, protein engineering of phosphotriesterase (PTE) was aimed to improve the specificity. Employing rational design and site-directed mutagenesis, we generated a small library comprising 24 variants for activity screening. Notably, W131M and I106A/W131M variants demonstrated successful preparation of pure (Sp)-diastereomer of remdesivir and sofosbuvir precursors within a remarkably short hydrolysis time (<20 min). Our work unveils a promising methodology for producing pure stereoisomeric compounds, utilizing novel biocatalysts to enable the chemoenzymatic synthesis of phosphoramidate nucleoside prodrugs.